Examining the Role of International Human Rights Tribunals in Promoting Accountability for Human Rights Violations - Yolanda Mona Salainti (The Easta Journal Law and Human Rights, 2023)
This study investigates the crucial role of international human rights courts in advancing accountability for human rights abuses. Its primary objective is to evaluate the effectiveness of these tribunals in holding accountable those — individuals, states, and non-state actors are to blame for major human rights violations. As part of the research methodology, relevant literature, case studies, and legal decisions from international human rights tribunals are thoroughly examined. The International Criminal Court (ICC), the International Court of Justice, and local human rights courts are all part of this. The scope of the investigation includes War crimes, genocide, and crimes against humanity, torture, and enforced disappearances. The findings underscore the substantial contribution made by international human rights courts in ensuring justice, truth-seeking, and redress for victims of human rights abuses. These tribunals have played a pivotal role in establishing legal precedents, clarifying the extent of human rights obligations, and fostering international cooperation to address impunity. The study also explores the challenges confronted by international human rights courts, including limited jurisdiction, enforcement capacity, and political opposition. Additionally, it examines potential synergies between international tribunals and national justice systems to strengthen accountability mechanisms at both the international and domestic levels. The findings of this study have significant implications for policymakers, individuals who advocate for human rights, and those who work in the legal field because they highlight the importance of a powerful and independent international human rights court in promoting accountability and providing justice for victims of human rights violations all over the world.